Darrieus wind turbine prototype control study - Pereira, Tobias (2019)
This paper focuses on control of a Darrieus vertical axis wind turbine prototype. Throughout this work a control strategy is proposed and a methodology is presented in order to achieve a solid foundation for the control process. A non linear dynamic model of the Darrieus prototype equipped with a permanent magnet synchronous generator was developed. The model was linearized and some controllers are developed, namely a PID controller and a Linear Quadratic Regulator. The controllers were tested in the linear and non linear models.